\[\boxed{\mathbf{1058}\mathbf{.}}\]
\[\frac{\sin^{2}a}{\cos a(1 + ctg\ a)} -\]
\[- \frac{\cos^{2}a}{\sin a(1 + tg\ a)} =\]
\[= \frac{2\sqrt{2}\sin\left( a - \frac{\pi}{4} \right)}{\sin{2a}}\]
\[1)\ \frac{\sin^{2}a}{\cos a(1 + ctg\ a)} -\]
\[- \frac{\cos^{2}a}{\sin a(1 + tg\ a)} =\]
\[= \frac{\sin^{2}a \bullet \sin a}{\cos a\left( 1 + \frac{\cos a}{\sin a} \right) \bullet \sin a} -\]
\[- \frac{\cos^{2}a \bullet \cos a}{\sin a\left( 1 + \frac{\sin a}{\cos a} \right) \bullet \cos a} =\]
\[= \frac{\sin^{3}a}{\cos a\left( \sin a + \cos a \right)} -\]
\[- \frac{\cos^{3}a}{\sin a\left( \sin a + \cos a \right)} =\]
\[= \frac{\sin^{3}a \bullet \sin a - \cos^{4}a \bullet \cos a}{\cos a \bullet \sin a \bullet \left( \sin a + \cos a \right)} =\]
\[Что\ и\ требовалось\ доказать.\]